2022
DOI: 10.2166/9781789062694
|View full text |Cite
|
Sign up to set email alerts
|

Jar Tests for Water Treatment Optimisation

Abstract: The book is intended as a handbook providing detailed instructions for the correct conducting of jar tests, which are needed for the optimisation of the coagulation/flocculation process. It contains the essential theoretical background of coagulation/flocculation, including a description of the influence of different parameters on the coagulation efficiency of various impurities (e.g. pH value and type/dose of coagulant), and floc properties and their separation (e.g. mixing intensity, mixing time, but also ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Doses higher than 9.62 mM were also used, but were not found to be effective. This can be explained by the fact that at a high coagulant dosage, saturation occurs where the particles no longer form flocs and therefore sink to the bottom along with the textile fibers [18].…”
Section: Effects Of Coagulation On Textile Fibers Removal Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Doses higher than 9.62 mM were also used, but were not found to be effective. This can be explained by the fact that at a high coagulant dosage, saturation occurs where the particles no longer form flocs and therefore sink to the bottom along with the textile fibers [18].…”
Section: Effects Of Coagulation On Textile Fibers Removal Efficiencymentioning
confidence: 99%
“…The removal of particles at higher pH values is mainly due to the adsorption of particles on Fe/Al precipitates. Previous studies showed that PACl is effective at slightly acidic pH, but also at higher pH values, which depends on the properties of the matrix [18].…”
Section: Introductionmentioning
confidence: 98%